Current and emerging strategies for management of myelodysplastic syndromes. (July 2021) - Saygin, Caner; Carraway, Hetty E.
Abstract: Myelodysplastic syndromes (MDS) are characterized by ineffective hematopoiesis with varying degrees of dysplasia and peripheral cytopenias. MDS are driven by structural chromosomal alterations and somatic mutations in neoplastic myeloid cells, which are supported by a tumorigenic and a proinflammatory marrow microenvironment. Current treatment strategies for lower-risk MDS focus on improving quality of life and cytopenias, while prolonging survival and delaying disease progression is the focus for higher-risk MDS. Several promising drugs are in the horizon, including the hypoxia-inducible factor stabilizer roxadustat, telomerase inhibitor imetelstat, oral hypomethylating agents (CC-486), TP53 modulators (APR-246 and ALRN-6924), and the anti-CD47 antibody magrolimab. Targeted therapies approved for acute myeloid leukemia treatment, such as isocitrate dehdyrogenase inhibitors and venetoclax, are also being studied for use in MDS. In this review, we provide a brief overview of pathogenesis and current treatment strategies in MDS followed by a discussion of newer agents that are under clinical investigation.